PENDEKATAN PENDIDIKAN MULTIKULTURAL SEBAGAI RESOLUSI KONFLIK DI INDONESIA - Irsyaadul 'Ibaad; Fita Triyana; Rachmad Sukriyanto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
Indonesia is a very large country with cultural diversity from east to west. The right intermediary or media to communicate learning in the form of Pancasila values and the principles of state and nation life is education, especially multicultural education. The purpose of this research is to find out which approach to multicultural education is suitable to be applied in Indonesia. This research uses a qualitative approach with library research, but the data analysis method used is content analysis. Multicultural education can be defined as cultural diversity education that responds to demographic and cultural changes within a particular community or the world as a whole. There are many types of multicultural conflicts in Indonesia: individual conflicts, social conflicts, racial conflicts, religious conflicts, family conflicts, and cultural conflicts. Other ways to resolve disputes include: the victory of one party over another, compromise between the warring parties, reconciliation between the warring parties, forgiving the other party from one side, conflict-free agreements. Multicultural education in Indonesia is more appropriate and suitable to be used as an educational approach. To implement multicultural education, several approaches can be used in the implementation process, namely the contribution approach, additive approach, transformation approach, and social action approach. This approach is applied by integrating the values of multicultural education in learning materials and in school culture.